ANALISIS GENDER DALAM KEHIDUPAN KELUARGA NELAYAN DI KECAMATAN PANGANDARAN KABUPATEN CIAMIS - Kusumo, Rani Andriani Budi; Charina, Anne; Mukti, Gema Wibawa (Jurnal Social Economic of Agriculture, 2013)
The study, entitled "Gender Analysis in Families Life Fishermen in Pangandaran Ciamis district" was conducted over eight months. The purpose of this study was to: 1) Assess the socio-economic characteristics of fishermen families in the District of Pangandaran Ciamis district.; 2) analyze the pattern of decision-making and the division of labor between husband and wife in a family of fishermen in the domestic sector and the public. This study uses survey method. The respondents consisted of 30 families of fishermen. Data were analyzed descriptively to create a systematic picture, factual and accurate statement of the facts, properties and relationships studied phenomenon objectively. The results showed that the level of education the majority of families of fishermen included in the low category. Perceptions of gender on family fishing generally illustrates that the main task the wife is the household, but it may help her husband in making a living family, while earning a living primary responsibility remains the task of the husband. Decision-making concerning the domestic activities and the public in a family of fishermen do not follow a particular pattern is specifically focused on the husband or wife, but it has a pattern that spreads between husband and wife. The task sharing concerning the domestic activities mostly done by the wife. While the division of labor associated with public activities spread between husband and wife. Keywords: gender, task sharing management, decision-making pattern